Arti (Art of Innovation) - MELLARA, Fernanda Nemetti; COSTA, Marina Batista; SOUSA, Vitória Martins (129, 2023)
O presente trabalho apresenta um plano de negócio inovador para a empresa ARTI (ART OF INNOVATION), o acrônimo representa a Arte da Inovação. A empresa oferece soluções tecnológicas que transcendem a simples criação de apresentações personalizadas. O objetivo deste plano de negócio é atender às necessidades de profissionais ocupados, desde o ambiente educacional até o ambiente empresarial, que enfrentam desafios ao criar apresentações de qualidade. O desenvolvimento do plano de negócio abrange diversas etapas, incluindo análise de mercado, definição de público-alvo, estratégias de marketing, financeiras, bem como a projeção de resultados. Além disso, são apresentadas explorações detalhadas realizadas ao longo do desenvolvimento do plano de negócio, evidenciando a viabilidade e potencial de crescimento da ARTI no mercado de soluções tecnológicas para apresentações.

This work presents an innovative business plan for the company ARTI (ART OF INNOVATION), the acronym represents the Art of Innovation. The company offers technological solutions that go beyond the simple creation of personalized presentations. The objective of this business plan is to meet the needs of busy professionals, from educational to business environments, who face challenges in creating quality presentations. The development of the business plan covers several stages, including market analysis, target audience definition, marketing and financial strategies, as well as projection of results. Furthermore, detailed explorations carried out throughout the development of the business plan are presented, highlighting ARTI's viability and growth potential in the market for technological solutions for presentations.
Arti (Art of Innovation)
Keywords: Empresas; Marketing; Gestão e Negócios